Respuesta :

The first term of this series (a+1) is 1 and the common ratio (r) is -3.

Thus, the explicit formula is a_n = 1*(-3)^(n-1).

Must check this!  suppose we try to calculate the 3rd term.  Then n = 3.

a_3 = 1*(-3)^(3-1) = (-3)^2 = 9.  This is correct.

Answer:

[tex]a_n=1\cdot (-3)^{(n-1)}[/tex]

Step-by-step explanation:

We have been given a geometric sequence and we are asked to find the explicit formula for our given sequence.

The explicit formula of geometric sequence is in form: [tex]a_n=a_1\cdot r^{(n-1)}[/tex], where,

[tex]a_n=\text{nth term of sequence}[/tex],

[tex]a_1=\text{1st term of sequence}[/tex],

[tex]r=\text{Common ratio}[/tex],

[tex]n=\text{Number of term}[/tex].

First of all, let us find common ratio of our given sequence by dividing one term by its previous term.

[tex]r=\frac{-3}{1}=-3[/tex]

We can see that 1st term of our given sequence is 1. Upon substituting our given values in explicit form of geometric sequence we will get,

[tex]a_n=1\cdot (-3)^{(n-1)}[/tex]

Therefore, the explicit formula for our given sequence is [tex]a_n=1\cdot (-3)^{(n-1)}[/tex].

ACCESS MORE